2018
DOI: 10.1016/j.omtn.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

One-Vector System for Multiplexed CRISPR/Cas9 against Hepatitis B Virus cccDNA Utilizing High-Capacity Adenoviral Vectors

Abstract: High-capacity adenoviral vectors (HCAdVs) devoid of all coding genes are powerful tools to deliver large DNA cargos into cells. Here HCAdVs were designed to deliver a multiplexed complete CRISPR/Cas9 nuclease system or a complete pair of transcription activator-like effector nucleases (TALENs) directed against the hepatitis B virus (HBV) genome. HBV, which remains a serious global health burden, forms covalently closed circular DNA (cccDNA) as a persistent DNA species in infected cells. This cccDNA promotes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 68 publications
(96 reference statements)
0
58
0
Order By: Relevance
“…CRISPR/Cas9, an accurate DNA editing technology can be used to mutate the cccDNA in order to destabilize the structure [285]. A recent study by Schiwon et al demonstrated that the CRISPR/Cas9-based system is capable to inhibit HBV replication [286]. However, the low concentrations of cccDNA in patients limit the effective targeting of CRISPR/Cas9 system, analysis of treatment, and potential off-targeting effects that affect the successful implementation of CRISPR/Cas9 system [285].…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9, an accurate DNA editing technology can be used to mutate the cccDNA in order to destabilize the structure [285]. A recent study by Schiwon et al demonstrated that the CRISPR/Cas9-based system is capable to inhibit HBV replication [286]. However, the low concentrations of cccDNA in patients limit the effective targeting of CRISPR/Cas9 system, analysis of treatment, and potential off-targeting effects that affect the successful implementation of CRISPR/Cas9 system [285].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, degrading cccDNA is an attractive strategy that is likely to cure occult HBV infection and abolish the risk of HBV reactivation. All candidates targeting cccDNA editing strategies, including zinc finger nucleases,184 transcription activator-like effector nucleases,185 and CRISPR/Cas9 systems186187 are effective in pre-clinical studies but have not yet been evaluated by clinical trials.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…Hence, HBV cccDNA is an optimal target for nuclease gene editing, due to its episomal minichromosome configuration and sequence stability. More specifically, the efficacy of CRISPR/Cas9 for cleavage and inactivation of the cccDNA, as well as inhibition of hepatocarcinogenesis, has been reported [ 34 , 35 ].…”
Section: Direct Acting Antiviralsmentioning
confidence: 99%